Land Suitability Evaluation for Rubber Cultivation on Hilly Land in Nagari Sitanang, Lareh Sago HalabanDistrict, Lima Puluh Kota Regency, West Sumatra - Riza Syofiani; Dyah Puspita Sari; Giska Oktabriana (Postgraduate, University of Mataram, 2026)
This study was conducted to identify the soil characteristics of hilly land, determine the actual and potential land suitability classes for rubber (Hevea brasiliensis), and identify the dominant limiting factors and their respective amelioration measures. The research employed a descriptive survey method involving field observation, soil sampling, laboratory analysis, and a land characteristic matching procedure against the growth requirements of rubber. Four land units were evaluated based on climate, water availability, drainage, root zone media, nutrient retention, erosion hazard, flood hazard, and land preparation. The findings revealed that rainfall, drainage, soil texture, soil depth, flood hazard, surface rock fragments, and rock outcrops were conducive to rubber growth. The principal limiting factors included an annual temperature of 22 °C, acidic to strongly acidic soil pH, low base saturation, low organic carbon content on steep slopes, a high coarse fragment content, and a high erosion hazard. The actual suitability classes obtained were S3-tc,nr for Unit A; S3-tc for Unit B; S3-tc,nr,eh for Unit C; and N-eh for Unit D. Following improvement interventions, Units A and B were upgraded to S2-tc, Unit C remained classified as S3-tc,eh, and Unit D remained classified as N-eh. Based on these results, rubber cultivation is recommended to be prioritized on Land Units A and B, implemented on a limited scale on Land Unit C with the application of intensive soil conservation practices. It is not recommended for Land Unit D due to its permanent topographical constraints.